(untitled) (Research, Society and Development, 2022)
Introduction: Chlorhexidine oral decontamination protocols are the usual care offered to patients in Intensive Care Units (ICU). The admission evaluation performed by dentists is absent from the routine, leading the medical team to overlook oral diseases, as they are rarely the main cause of hospitalization and the common absence of pain or other symptoms. Healthy or not, the oral cavity has an extensive reservoir of pathogens and can spread systemic infections and modify or worsen the general health of hospitalized patients. Methods: We conducted a prospective longitudinal study in the general ICU of Hospital Sírio Libanês, in São Paulo. Oral health was assessed at admission, three, and seven’s day of hospitalization by clinically (bedside oral examination (BOE), plaque and mucosa index (MPS), presence of infectious foci) and microbiologically indexes(identification of microorganisms in saliva and biofilm).Results: Sixty patients were initially included, with 70% of oral care dependency, and 39.47% were admitted and remained with oral infectious foci throughout the study. 38 patientes clinically followed presented improvement in BOE and MPS indices. With no statistically significant differences between saliva and biofilm during the hospital stay, 27 patients had a prevalence of Candida spp, ESKAPE (E. faecalis, S.aureus, K.pneumoniae, A.baumannii, P.mirabilis, and Enterobacter spp.) and pathogens associated with nosocomial pneumonia (S.aureus, K.pneumoniae, P.aeruginosa, E.cloacae, P.mirabilis, Streptococcus spp, E.coli, H.influenza, and S.pneumoniae). Conclusion: In addition to nursing care, oral assessment at hospital admission and dental follow-up can align patients’ oral hygiene protocols with their real systemic needs.